2022
DOI: 10.3389/fpubh.2022.1012727
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of e-cigarette marketing on social media: Findings from the Tobacco Enforcement and Reporting Movement (TERM) in India, Indonesia and Mexico

Abstract: BackgroundThe use of e-cigarettes is proliferating globally, especially among youth and even children. Marketing is a known risk factor for e-cigarette initiation, yet little is known of e-cigarette marketing on social media in low- and middle-income countries. This study compares e-cigarette social media marketing in India, Indonesia, and Mexico, three such countries with different regulatory environments.MethodsInstances of e-cigarette marketing on social media platforms were identified via the Tobacco Enfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 47 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Online marketing and sales of e-cigarette are well-established strategies of tobacco companies [11,25,26]. Hence several researchers have studied online marketing, and content analyses of social media websites [25,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Online marketing and sales of e-cigarette are well-established strategies of tobacco companies [11,25,26]. Hence several researchers have studied online marketing, and content analyses of social media websites [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…Claims about lifestyle bene ts of e-cigarette such as making claims of improved social status, modernity are reported in previous studies [11,[14][15][16]]. In addition, the claims about affordability, convenience, are aimed to encourage uptake of e-cigarette by the non-smoking youth and young adults by making ecigarette appear as healthier, less risky, and socially appealing.…”
Section: Marketing Claims Reported Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Advertisements for e-cigarettes in India continue to be broadcast on social media through third-party retailers. The Indian market actually provides customers with covert options for buying e-cigarettes through phone numbers and WhatsApp (Murukutla et al 2022).…”
Section: Implications Of the Ban And Its Current Statusmentioning
confidence: 99%
“…In India, 86% of e-cigarette advertisements on social media focused on attractive product features such as novel device designs, flavours, touch screen indicators, and product customizability (Murukutla et al 2022). The study found that compared to Mexico and Indonesia, India had the highest engagement with social media posts that emphasised such product features.…”
Section: E-cigarette Usage Is Minimal In Indiamentioning
confidence: 99%